Retaining Employees Amidst Waves of Change: A Study on Organizational Culture Post-Acquisition - Maulana, Syahrial; Sukmawati, Anggraini; Nurhayati, Popong; Sumarwan, Ujang (Jurnal Aplikasi Manajemen, 2025)
In the context of globalization, company acquisitions are a common strategic move; however, the post-acquisition phase often brings challenges, especially in organizational culture integration and employee retention. This study explores how organizational culture integration after acquisition affects employees' decisions to remain in the organization. Using a qualitative case study approach, data were collected through in-depth interviews with employees who experienced the acquisition process at an oil and gas company in Indonesia. The findings reveal that transparent communication, recognition of employee concerns, and opportunities for growth significantly contribute to employee retention. Moreover, psychological and emotional aspects such as perceived security, cultural compatibility, and inclusive leadership emerge as key influencing factors. The study highlights the need for empathetic, structured, and inclusive integration strategies as part of effective human resource management practices to enhance post-acquisition employee retention.